Optical coherence tomography angiography in glaucoma: a mini-review [version 1; referees: 2 approved] - Kelvin H. Wan (F1000Research, 2017)
The advent of optical coherence tomography angiography (OCT-A) provides a new opportunity to visualize the retinal vasculature in a non-invasive and dye-free manner which may help identify vascular abnormalities in glaucoma. While a reduction in retinal and optic nerve head vessel densities and blood flow indexes measured by OCT-A has been demonstrated in patients with glaucoma in many studies, it is unclear whether OCT-A provides additional information for the detection and monitoring of glaucoma compared with OCT measurements such as retinal nerve fiber layer thickness, neuroretinal rim width, and ganglion cell inner plexiform layer thickness. Longitudinal studies are needed to elucidate whether vascular abnormalities detected by OCT-A are a cause or a consequence of optic nerve damage in glaucoma.